Pengaruh Literasi Keuangan, Perilaku Keuangan, Locus of Control dan Faktor Demografi terhadap Keputusan Investasi - Dhea Kurnela; Hari Setiono; Nurdiana Fitri Isnaini (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
This study aims to determine the effect of financial literacy, financial behavior, locus of control, and demographic factors on investment decisions. This research is quantitative type. The population in this study were tutors of Alhimni Education Center (AEC), Ngoro Mojokerto, totaling 39. The sampling technique used non-probability sampling method with saturated sample technique. Data collection techniques in this study using primary data, the instrument in this study using a questionnaire through google form with measuring instruments in the form of a Likert scale and ordinal scale. The analysis technique used in this research is descriptive statistical analysis, data quality test, classical assumption test, multiple linear regression analysis test, t test, F test and coefficient of determination with the help of SPSS software program version 22. The results showed that financial literacy, education had an effect on investment decisions, while financial behavior, locus of control, and income had no effect on investment decisions.